The Effects of Cytokines on Spontaneous Hepatitis B Surface Antigen Seroconversion in Chronic Hepatitis B Virus Infection - Wu, Jia-Feng; Hsu, Hong-Yuan; Chiu, Yu-Chun; Chen, Huey-Ling; Ni, Yen-Hsuan; Chang, Mei-Hwei (The Journal of immunology (1950), 2015)
We examined the role of human cytokines in the natural course of hepatitis B surface Ag (HBsAg) seroconversion in chronic hepatitis B virus (HBV) infection. The clinical course of spontaneous HBsAg seroconversion was assessed in 296 chronically HBV-infected patients. Single nucleotide polymorphisms (SNPs) in IL-1β, IL-2, IL-4, IL-10, IL-12β, IL-13, IL-27, and IFN-γ genes were examined in 296 chronically HBV-infected patients and another 193 HBV recoverers. The HBsAg a determinant sequence of chronically HBV-infected subjects with and without HBsAg seroconversion was also analyzed. The start of the immune-clearance phase (serum alanine aminotransferase levels > 30 IU/l) before the age of 48 mo and hepatitis B e Ag (HBeAg) seroconversion before the age of 10 y predicted spontaneous HBsAg seroconversion in chronically HBV-infected patients (odds ratios 17.7 and 5.0; p < 0.001 and p < 0.002, respectively). The A-allele of IL-10 SNP rs1800872 was associated with higher IL-10 serum levels, and the G-allele of IL-12β SNP rs3212217 was associated with sustained high serum IL-12p70 levels during the immune-clearance phase. Both were predictors of spontaneous HBsAg seroconversion and HBV recovery (odds ratios 4.0 and 26.3; p = 0.002 and p < 0.001, respectively). Spontaneous HBsAg seroconversion was not related to sex, HBV genotype, or HBsAg a determinant mutation. The start of immune-clearance phase, age at HBeAg seroconversion, and serum IL-10 and IL-12 levels are associated with the course of the immune-clearance phase in chronic HBV infection, and are predictive of spontaneous HBsAg seroconversion and HBV recovery.